Gambaran Sensitivitas Antibiotik Yang Diresepkan Pada Pasien Ulkus Diabetikum Di RSUD Kraton Kabupaten Pekalongan - Intan Meilalita; Mulia Susanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Diabetic ulcer is a complication of peripheral neuropathy in people with diabetes mellitus which often ends in disability or death. Proper handling of infection is closely related to the rational use of antibiotics to avoid the occurrence of resistance. The emergence of resistance to antibiotics has an effect on the risk of increasing infection status, increasing the length of stay in the hospital, the risk of amputation and even death. Objectives: This study aims to determine the type and percentage of bacteria present in diabetic ulcers and to test the sensitivity of antibiotics prescribed in diabetic patients with ulcers in the inpatient room of RSUD Kraton, Pekalongan Regency. Methods: The research model used was descriptive to describe the profile of bacteria and the sensitivity of antibiotics prescribed to bacterial findings from diabetic ulcer isolates in inpatients at Kraton Hospital, Pekalongan Regency. The research method was carried out by biochemical identification and sensitivity testing of the Kirby Bauer technique on 2 samples of diabetic patients with ulcer complications taken by total census during March-April 2022. Results: Staphylococcus aureus, Enterobacter aerogenes, Pseudomonas aeruginosa were found with a percentage of 50% each. The sensitivity test showed that Ampicillin was resistant to Staphylococcus aureus, Ciprofloxacin was resistant to Enterobacter aerogenes and intermediate to Pseudomonas aeruginosa. The percentage of effectiveness of Meropenem and Metronidazole antibiotics had the highest sensitivity values, namely 100%, 50% Ampicillin and 25% Ciprofloxacin. Conclusion: From the research that has been done, it can be concluded that Ampicillin is resistant to Staphylococcus aureus, Ciprofloxacin is resistant to Enterobacter aerugenes, Ciprofloxacin intermediate is resistant to Pseudomonas aeruginosa, Meropenem and Metronidazole are sensitive to the three bacterial findings namely Staphylococcus aureus, Enterobacter aerogenes, Pseudomonas aeruginosa